'This is my cheating ex': Gender and sexuality in revenge porn. (September 2019) - Hearn, Jeff; Hall, Matthew
Revenge pornography is the online, and at times offline, non-consensual distribution, or sharing, of explicit images by ex-partners, partners, others, or hackers seeking revenge or entertainment. In this article, we discursively analyse a selected range of electronic written texts accompanying explicit images posted by self-identified straight/gay/lesbian (male-to-female, female-to-male, male-to-male, female-to-female postings) on a popular revenge pornography website 'MyEx.com'. Situating our analysis in debates on gender and sexuality, we examine commonalities and differences in the complex and sometimes contradictory ways in which gender and sexuality are invoked in posters' accounts of their motivations for revenge pornography.